Media Illustration of Storybooks and Video Barcodes in an Effort to Improve Listening Ability of Kindy B Students - Siti Fatimah; Ida Yeni Rahmawati; Betty Yulia Wulansari (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2022)
This research aims to (1) develop a media story book illustration and barcode videos in an effort to increase the listening ability to the kindy B’s students in Mutiara Hati Kindergarten. (2) find out the difference between before and after using a media story book illustration and a barcode video. The study used the research method research and development (rd). Data is collected using authentic test assessments, interviews and angkets. Qualitative data are analysed in a descriptive way from interviews and expert advice on validation, the quantitative data comes from the expert validation and authenticated testing methods of pre-experimental experimentation in the form of one group preposttest. The results of this study are (1) a media story book illustration and a barcode video entitled "Kue Boni Untuk Nenek" in which a story consists of a book barcode containing videos in it in an effort to improve the listening ability to the kindy B’s students in Mutiata Hati Kindergarten. Validation value by a material expert in 90% is categorized as valid and by a validation value media expert at 82.5% is categorized as valid. (2) there is a difference in students' ability to listen between before and after using a media story book illustration and a barcode video. At a small scale test in pretest got 45.71 score is categorized less than at score posttest of 79.14 is categorized as good with 33,43% discrepancies. Then, at a large scale test, got 62.6 score is categorized average and at a posttest of 84.6 is categorized as good with 22% discrepancies. Developing media story book illustration and barcode videos entitled "Kue Boni Untuk Nenek" can enhance the listening ability to the Kindy B’s students in Mutiara Hati Kindergarten of Ponorogo.